Effect of Biochar on Yield and Quality of Potato (Solanum tuberosum) Tuber - Mollick, Md. Omar Ali; Paul, Alok Kumar; Alam, Ishrat; Sumon, Munshi Mohammad (International Journal of Bio-resource and Stress Management, 2020)
A field experiment was conducted in Sher-e-Bangla Agricultural University (SAU), Dhaka, Bangladesh during the period from November, 2017 to March, 2018 in rabi season to observe the effect of biochar on the yield and quality of potato tuber and to find out the optimum dose of biochar along with inorganic fertilizer for achieving the maximum yield of potato. The experiment consist of 9 treatments as Control (no chemical fertilizer and biochar), Recommended Fertilizer Dose; Recommended Fertilizer Dose+Biochar @ 2.5 t ha-1; Recommended Fertilizer Dose+Biochar @ 5.0 t ha-1; Recommended Fertilizer Dose+Biochar @ 7.5 t ha-1; 1/2 of Recommended Fertilizer Dose+Biochar @ 2.5 t ha-1; ½ of Recommended Fertilizer Dose+Biochar @ 5.0 t ha-1; ½ of Recommended Fertilizer Dose + Biochar @ 7.5 t ha-1; Biochar @ 10 t ha-1. The experiment was laid out in a Randomized Complete Block Design with three replications. The tested variety was BARI Alu-7 (Diamant). Data were collected on different yield attributes, growth and quality of potato and postharvest soil analysis. The results indicated that biochar application significantly (p<0.05) increased plant height, weight of tubers, yield of tubers, tuber dry matter content, tuber specific gravity, soil organic carbon. Results suggested that biochar application had significant positive effect on plant and soil.